A release-and-capture mechanism generates an essential non-centrosomal microtubule array during tube budding - Ghislain Gillard (Nature Portfolio, 2021)
Non-centrosomal microtubules provide essential functions in many cells, but the mechanisms of their formation are poorly understood. Here, the authors show that during tube formation of the Drosophila salivary glands, microtubules are released from a single active centrosome via katanin, triggering recruitment of Patronin, and leading to formation of a non-centrosomal network key to the tube invagination process.